CAMPFIRE - the political ecology of poverty alleviation, wildlife utilisation and biodiversity conservation in Zimbabwe - Vorlaufer, Karl (ERDKUNDE, 2002)
The Communal Areas Management Programme for Indigenous Resources was initiated with the main goal of alleviating poverty in peripheral rural areas of Zimbabwe that have an abundance of wildlife. This was to be achieved by granting to the rural communities the right to the sustainable use of wildlife. It is expected that the people will protect this resource, which they are allowed to use, and that thus large populations of different species of wildlife will be preserved long-term. The study revealed that a large number of actors are involved in the programme at different hierarchical levels and that they often have differing or even contradictory interests. In some districts there has actually been a precipitous rise in CAMPFIRE revenues in the past ten years, especially from hunting tourism. Nevertheless, in all districts this revenue is rather modest, and it has not alleviated the serious poverty of the programme’s target group, the rural population. Because the populations of game are large and growing, the conflicts between humans and wildlife are increasing; the modest CAMPFIRE revenue cannot compensate for the costs of the large amount of damage caused by wildlife. Nor has the goal of empowerment, of promoting grass roots development, been reached to any great degree so far, partly because the decisions, especially about the distribution of revenue, are made from the top down. The biodiversity, especially the large diverse populations of wildlife, have, however, been protected and have even expanded, partly because the sport hunting is done in a sustainable manner, and the hunting quotas are far lower than the reproduction rates.